2022
DOI: 10.1097/j.jcrs.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of transepithelial photorefractive keratectomy with epithelial ablation targeting actual epithelial thickness vs default laser platform values

Abstract: In transepithelial PRK, refractive outcome depends little on preexisting corneal epithelial thickness. There is a concern about the contraction of OZ, especially in lower intended ablations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Using VHFU technology, Reinstein et al showed that the average central CET was 53.4 ± 4.6 μm, comparable with SD-OCT [22]. Using SD-OCT, normal CET profles were described to be thicker in the central 2 mm of the cornea ranging from 53 to 54 μm in the center and decreased with a low gradient of −0.43 μm/mm toward 7 mm midperiphery and a larger gradient of −2.31 μm/mm toward 9 mm periphery [45,52,60,[71][72][73]; VHF-US studies did not fnd such thinning trends [22].…”
Section: Corneal Epithelium In Normal Eyesmentioning
confidence: 69%
See 1 more Smart Citation
“…Using VHFU technology, Reinstein et al showed that the average central CET was 53.4 ± 4.6 μm, comparable with SD-OCT [22]. Using SD-OCT, normal CET profles were described to be thicker in the central 2 mm of the cornea ranging from 53 to 54 μm in the center and decreased with a low gradient of −0.43 μm/mm toward 7 mm midperiphery and a larger gradient of −2.31 μm/mm toward 9 mm periphery [45,52,60,[71][72][73]; VHF-US studies did not fnd such thinning trends [22].…”
Section: Corneal Epithelium In Normal Eyesmentioning
confidence: 69%
“…In a contralateral eye study, our team compared the effect of programming the laser device with the actual CET profile in the center and periphery for T-PRK in virgin right eyes compared to the default protocol of the device, which considered CET 55 μ m in the center and 65 μ m in the periphery in the left eye. We did not find a significant difference in wasted tissue, but slightly hyperopic results and more contracted optical zones were noted [ 72 ].…”
Section: Refractive Surgerymentioning
confidence: 96%
“…The real value of Table 2 is that the analysis of postoperative results is based on a huge amount of data. To our knowledge, no analysis of such a large amount of data has previously been published in the literature [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%